ФАКТОРЫ РИСКА ПРОГНОСТИЧЕСКИ ЗНАЧИМЫХ НАРУШЕНИЙ СЕРДЕЧНОГО РИТМА ПРИ ДИСПЛАЗИИ СОЕДИНИТЕЛЬНОЙ ТКАНИ - А. В. Ягода; М. В. Новикова; Н. Н. Гладких (Архивъ внутренней медицины, 2015)
Joint hypermobility, increased left atrium and transaortic flood, chronic infection and astenovegetative syndrome were found more frequently in patients with connective tissue dysplasia and prognostic significant arrhythmias.